Isolated but (more) connected - Oliveira, Fabiana Lazzari de (2021)
The text presents issue no. 24 of Móin-Móin Magazine - Studies in The Arts ofPuppetry, with the theme Training experiences in cyberspace and creative processes in socialisolation. To do so, it raises the questions launched as a provocation to the authors of this calland gives a brief account of the migration of the activities of the Extension Program ProfessionalTraining in Santa Catarina’s Theater, in which the edition of the journal is inserted, for the virtualmode.